Features of cytomegalovirus DNAemia and virus‐specific T‐cell responses in allogeneic hematopoietic stem‐cell transplant recipients during prophylaxis with letermovir. Issue 2 (7th February 2023) - Giménez, Estela; Guerreiro, Manuel; Torres, Ignacio; Aguilar, Cristobal; Albert, Eliseo; Hernández‐Boluda, Juan Carlos; Hernani, Rafael; Pérez, Ariadna; Amat, Paula; Piñana, José Luis; Montoro, Juan; Solano, Carlos; et al.
Abstract: Background: There is scarce information on the natural kinetics of cytomegalovirus (CMV) DNAemia and dynamics of CMV‐specific T‐cell reconstitution in allogeneic hematopoietic transplant recipients (allo‐HSCT) undergoing letermovir (LMV) prophylaxis. Methods: Twelve adult CMV‐seropositive high‐risk recipients (median age, 53 years; 9 males/3 females) undergoing LMV prophylaxis and 13 non‐LMV allo‐HSCT controls (median age, 58 years; 7 males/6 females) were included. CMV DNAemia in plasma was monitored by real‐time polymerase chain reaction. Preemptive antiviral therapy (PET) was administered upon detection of ≥1500 IU/ml. CMV‐specific interferon‐gamma (IFN‐γ)‐producing CD8 + and CD4 + T cells were enumerated by flow cytometry around days +30, +60, and +90 after allo‐HSCT. Ex vivo experiments assessing of the potential effect of LMV on CMV‐specific T‐cell expansion in a single CMV‐seropositive donor were also conducted. Results: Five LMV patients (41.6%) developed CMV DNAemia that cleared spontaneously. Four patients (33.3%) developed CMV DNAemia after LMV cessation, of which two required PET. Nine non‐LMV patients (69.2%) developed CMV DNAemia (five required PET). The percentage of LMV and non‐LMV patients exhibiting detectable CMV‐specific T‐cell responses was comparable (7/10 vs. 10/13; p = .71). Nevertheless, median CMV‐specific CD4 + and CD8 + T‐cell counts were lower in LMV patients by days +60 ( p = .006 and .02, respectively) and +90 ( p = .08 and .02). Ex vivo, CMV‐specific CD8 + T cells expanded to the same level either in the presence (19.8%) or in the absence of LMV (20.6%). Conclusions: In our series, episodes of CMV DNAemia in LMV patients cleared spontaneously. A diminished degree of CMV‐specific T‐cell reconstitution in LMV patients compared to non‐LMV patients was observed. Abstract :